2022
DOI: 10.21608/puj.2022.138041.1166
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the prophylactic and therapeutic effects of curcumin nanoemulsion in comparison with Spiramycin in mice simulating acute infection with T. gondii (RH strain)

Abstract: Background: Currently, there is no effective adjunct to therapeutic drugs against acute toxoplasmosis. Curcumin (CUR) is one of the most promising naturally occurring agents with anti-inflammatory, antioxidant, and anti-carcinogenic activity. It is hypothesized that improvement of CUR properties utilizing nanotechnology may be beneficial in enhancing its therapeutic effects. Objective: To evaluate the prophylactic immunostimulatory and therapeutic effects of CUR nanoemulsion in acute toxoplasmosis in experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…While both spiramycin and BPQ treatments couldn't reduce the deaths significantly. In this study, the infected non-treated group showed a MR of 41.6% which is in agreement with Rageh et al (2022) who reported a 40% mortality rate in the infected non-treated group. However, they reported no deaths in the group treated with spiramycin which may be explained by infecting the mice orally with only 20 cysts of the ME49 strain compared to 100 cysts of the same strain used in our study, and the euthanasia day of mice was on the 9 th week compared to the 70 th day of our experiment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…While both spiramycin and BPQ treatments couldn't reduce the deaths significantly. In this study, the infected non-treated group showed a MR of 41.6% which is in agreement with Rageh et al (2022) who reported a 40% mortality rate in the infected non-treated group. However, they reported no deaths in the group treated with spiramycin which may be explained by infecting the mice orally with only 20 cysts of the ME49 strain compared to 100 cysts of the same strain used in our study, and the euthanasia day of mice was on the 9 th week compared to the 70 th day of our experiment.…”
Section: Discussionsupporting
confidence: 92%
“…All treatment regimens used in the present study reduced the number of T. gondii cysts in comparison to the infected non-treated group. Similarly, Grujić et al (2005) and Rageh et al (2022) reported a significant reduction of ME49 brain cyst burden after treatment with spiramycin compared to the control group. Likewise, Gamea et al (2022) reported a highly significant reduction of RH strain tachyzoites numbers in peritoneal fluid and liver smears after CQ treatment.…”
Section: Discussionmentioning
confidence: 78%
“…Spiramycin was purchased from Sigma-Aldrich, Germany. Preparation, dose, and methods of administration were as previously described [38].…”
Section: Drugsmentioning
confidence: 99%
“…Drugs: Spiramycin and CUR were purchased from Sigma-Aldrich, Germany. Preparation, dose and methods of administration were previously described [10] .…”
Section: Experimental Animalsmentioning
confidence: 99%
“…Pilot study: As previously described [10] , a pilot study was conducted to determine the least effective dose of CUR nanoemulsion, and a dose of 20 mg/kg/d was established as the lowest effective dose.…”
Section: Preparation and Characterization Of Cur Nanoemulsionmentioning
confidence: 99%